Developing Reflective Thinking in Female Students Fourth Grade Preparatory School in the Subject of Quran oh Noble and Islamic Education - Abbas, Lina Naeem; Nida, Qasim MOhammed (Journal of Ecohumanism, 2024)
Developing reflective thinking in Female students Fourth-row Preparatory School in the Holy Quran and Islamic education. To achieve this goal, the hypothesis was formulated as Oh Zero. The following two: There are no statistically significant differences at the significance level (0.05) between the average scores of the female students in the group the Experimental Of those whom Y They studied Subject: The Holy Quran and Islamic education. The average grades of female students the Control group of those whom Y They studied Subject: The Holy Quran and Islamic education for method Traditional in Developing reflective thinking. Harmony Community Search present from Schools High school And middle school Daytime Governmental Affiliate For the directorate Public To raise The third Karkh For the year Academic2023/ 2024The research community consisted of (2548) female students. I chose intentionally(High school The Lights For Girls)To be a sample Search To apply Experience and I adopted a tool Search The represented With(a test Thinking Contemplative)For a substance The Qur’an The generous one And education Islamic a test(Mohammed,2017)And the component from(20)paragraph, from type choice from Multiple, It was completed Make sure from Believe it And its stability from during Show it on group from Arbitrators Their number is large(16)An arbitrator in the educational and psychological sciences. All paragraphs were calculated The two types of honesty coefficient (face validity and construct validity), as for Stability has been calculated In two ways : Analysis method Contrast using equation Qudr-Richardson(20)Which You measure bezel Consistency Internal For periods Testing And he found that Stability coefficient Testing It equals(88,0), as It was completed account Factories Constancy In a way Retail Midterm using equation Spearman-Brown So he reached Factories proof(0,82)And he Factories stability High used means Statistics The represented With(square Kay , Testing Al-Tai Damn Independent , equation Factories Difficulty And discrimination , equation effectiveness Alternatives wrong , Factories Link Duo Bullet , equation Qudr-Richardson(20), equation Cohen , square Eta To extract body Impact)And after to treat Data Statistically showed Results May come: excel performance Female students Group empiricism who In developing reflective thinking on Female students Group The female officers who studied on according to method Traditional. In light of the research results, it was presented! A set of recommendations and proposals, the most important. of which are the following: Conclusions: development Thinking Contemplative I have Female students group empiricism more from method Traditional. Recommendations: 1-Including exam questions for the final and unfinished levels in the Holy Quran and Islamic education. 2-Inclusion Curricula material The Qur’an The generous one and education Islamic in Colleges Education, strategic steps, draw your ideas.